2021
DOI: 10.3390/vaccines9020118
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Neutralized Nicotine Distribution Using Mice Vaccinated with the Mucosal Conjugate Nicotine Vaccine

Abstract: Tobacco smoking continues to be a global epidemic and the leading preventable cause of cancer and cardiovascular disease. Nicotine vaccines have been investigated as an alternative to currently available smoking cessation strategies as a means to increase rates of success and long-term abstinence. Recently, we demonstrated that a mucosal nicotine vaccine was able to induce robust mucosal and systemic antibodies when delivered heterologously using intranasal and intramuscular routes. Herein, we investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Indeed, antagonizing the effects of nicotine has shown promise in conjunction with varenicline, considered the most effective smoking cessation treatment available. Animal studies, especially in rats across laboratories and across specific vaccine compounds, have indicated that immunization leads to reduced nicotine penetration into the brain and diminished behavioral responses to nicotine, including locomotor effects [ 83 , 84 ]. However, the limited published human studies exploring various nicotine vaccines have not yet provided substantial evidence supporting vaccine efficacy as a treatment for nicotine dependence.…”
Section: Recent Progress In Anti-drug Vaccine Researchmentioning
confidence: 99%
“…Indeed, antagonizing the effects of nicotine has shown promise in conjunction with varenicline, considered the most effective smoking cessation treatment available. Animal studies, especially in rats across laboratories and across specific vaccine compounds, have indicated that immunization leads to reduced nicotine penetration into the brain and diminished behavioral responses to nicotine, including locomotor effects [ 83 , 84 ]. However, the limited published human studies exploring various nicotine vaccines have not yet provided substantial evidence supporting vaccine efficacy as a treatment for nicotine dependence.…”
Section: Recent Progress In Anti-drug Vaccine Researchmentioning
confidence: 99%